Electrospun Linear and Branched Nanofibrous Scaffolds for Potential Therapeutic Application in Melanoma. Issue 3 (2018) - Naves, Lucas B.; Dand, Chetna; Ong, Seow Theng; Gandhimathi, Chinnasamy; Venugopal, Jayarama Reddy; Almeida, Luis; Verma, Navin k.; Lakshminarayanan, Rajamani; Ramakrishna, Seeram
No abstract available